The Carpal Tunnel Syndrome: An experience in District and Tertiary Care Hospital Karachi (Journal of Pakistan Orthopaedic Association, 2014)
Objective: To describe the Clinical Presentation and surgical out come in patients, suffering from carpal Tunnel Syndrome. Study Design: Case series observational study. Duration: December 2008 to September 2011.Methodology: This Study includes only female patients with the signs and Symptoms of Carpal Tunnel Syndrome (CTS). The patient diagnosed as case of CTS on the basis of history and Clinical examination was subjected to nerve conduction studies. These patients followed up after 15 days, 3 Months and 6 Months of time period. Patients were advised Physiotherapy & Rehabilitation.Result: In this study a total of 36 female patients ranging in age from 20 to 60yrs, 26 had bilateral and 10 had unilateral disease. The diagnosis confirmed by Nerve Conduction Test. The 09 patients had mild sign and Symptoms, manage conservatively while 05 had moderate and 26 patients had the severe neuropathy with marked wasting of muscle, were operated. Eighty seven % (27 patients) of patients had marked improvement of Symptoms on first follow up.Conclusion: Carpal Tunnel Syndrome is predominantly the disease of middle-aged female. Open surgery is the treatment of choice for severe neuropathy, while mild and moderate types respond to medicine and physiotherapy.Keywords: Carpal tunnel Syndrome (CTS), Nerve Conduction study (NCS) Entrapment Neuropathy, Median Neurolysis.